Soil quality in native and cultivated areas in the Chapada in the Araripe in the semiarid of northeast brazil (Research, Society and Development, 2020)
Soil quality is related to its ability to perform functions that interfere with plant, animal and environmental productivity, arid and semi-arid regions are characterized by having soils with low fertility, poorly structured, with little water retention capacity, so that to know the quality of the soil and of fundamental relevance for the proper planning of its use and management. Studies on chemical indicators of soil quality in native and cultivated areas in Chapada in the Araripe, in the semi-arid region of northeastern Brazil are scarce, which can cause an improper management of agricultural areas, where the objective of this review was to gather and summarize information on quality of the land. soil in that region. The lack of more information on chemical quality indicators, exposes the region to the risk of degradation of cultivable areas through the use of inadequate management, and leaves open the need for further research on the chemical attributes and the quality of the soils of the plateau.